Penerapan Metode Pembelajaran Inkuiri Dalam Upaya Meningkatkan Hasil Belajar Siswa Pada Tema Kewajiban dan Hakku di Kelas III SD Negeri 206/X Pandan Jaya - Elizarita Elizarita (Departement of Mathematics Education, 2021)
This study aims to disclose information and discuss the application of a scientific approach in an effort to improve student learning outcomes on the theme of figures and inventions in class VI SD Negeri 113/X Pandan Makmur.This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 113/X Pandan Jaya. The time of this research was carried out in the odd semester of the academic year 2021 - 2022, which began in September 2021. The subjects in this study were class VI students, totaling 23 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing, and reflecting. Data collection in this study was carried out using observation sheets, field notes, learning outcomes test sheets, and documents. The data were analyzed using the percentage formula. The results of this study indicate that the scientific approach to the theme of figures and discoveries can improve student learning outcomes in grade VI SD Negeri 113/X Pandan Jaya which is marked by an increase from pre-cycle (22%), cycle I (57%), cycle II (91%).